INDUSTRIAL PERSPECTIVE ON MILLENNIAL WORKER COMPETENCE - Rahmawati, Devie; Anindhita, Wiratri; Lusia, Amelita; Wiwesa, Rangga; Viendyasari, Mila (Interaksi: Jurnal Ilmu Komunikasi, 2022)
This study aims to identify industry perspectives on Millennial Worker Competencies. The subject of qualitative research is a sample population of 60 industry professionals from the communication sector and start-up companies in job seekers. This research used qualitative data. Data collected through in-depth interviews. Based on the research results, it shows that graduates from higher education need skills to enter the world of work. The identification of an industrial perspective has implications for employee recommendations for the work competency curriculum framework in higher education. Third, a comprehensive evaluation of the attitudes and talents of workers in the digital age. Higher education institutions must increase their partnerships with industry, which is very important to improve human resources who have the competencies needed to compete globally.